The Exercise of Patriarchal Power and the Women’s Negotiation of Power in “The Arabian Nights” - Natalia Angel (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This study focuses on the four tales that are taken from The Arabian Nights, namely The Tale of King Shahryār and His Brother, The Tale of the Porter and The Three Young Girls of Baghdad, Ali Baba and the Forty Thieves, and Ali Shar and Zumurrud. The goal is to find the forms of patriarchal power as the causes of the women characters’ negotiation of power and also the forms of the women characters’ negotiation of power in The Arabian Nights. The theories that are used for this study are the theory of power relation, the concept of docile bodies, and the concept of negotiation of power/power strategies. From the analysis, it is found that in the patriarchal society of The Arabian Nights, power is fluid and not fixed. Thus, in the society of The Arabian Nights, the women can still show reactions against men’s exercise of patriarchal power. Key words: Power, Negotiation, Women, Patriarchy, Resistance, Rebellion.